The Pontryagin dual of the multiplicative group of positive rational numbers - Chaochao Sun; Yuanbo Liu (AIMS Mathematics, 2023)
The Pontryagin dual of the multiplicative group of positive rational numbers is constructed. Then we study its topological generators and representations.